Off the grid ebook - Box, C. J. (Joe Pickett, 2016)
Don’t miss the JOE PICKETT series—now streaming on Paramount+ The Red Desert of Wyoming is a beautiful and punishing place for anybody, even for game warden Joe Pickett and his friend Nate Romanowski in this #1 New York Times bestselling thriller... Nate is off the grid, recuperating from wounds and trying to deal with past crimes, when he is suddenly surrounded by a small team of elite professional special operators. They’re not there to threaten him, but to make a deal. They need help destroying a domestic terror cell in Wyoming’s Red Desert, and in return they’ll make Nate’s criminal record disappear. But they are not what they seem, as Nate’s friend Joe Pickett discovers. They have a much different plan in mind, and it just might be something that takes them all down—including Nate and Joe.